Recent Development of Moisture‐Enabled‐Electric Nanogenerators. Issue 46 (22nd September 2022) - Guan, Peiyuan; Zhu, Renbo; Hu, Guangyu; Patterson, Robert; Chen, Fandi; Liu, Chao; Zhang, Shuo; Feng, Ziheng; Jiang, Yue; Wan, Tao; Hu, Long; Li, Mengyao; et al.
Abstract: Power generation by converting energy from the ambient environment has been considered a promising strategy for developing decentralized electrification systems to complement the electricity supply for daily use. Wet gases, such as water evaporation or moisture in the atmosphere, can be utilized as a tremendous source of electricity by emerging power generation devices, that is, moisture‐enabled‐electric nanogenerators (MEENGs). As a promising technology, MEENGs provided a novel manner to generate electricity by harvesting energy from moisture, originating from the interactions between water molecules and hydrophilic functional groups. Though the remarkable progress of MEENGs has been achieved, a systematic review in this specific area is urgently needed to summarize previous works and provide sharp points to further develop low‐cost and high‐performing MEENGs through overcoming current limitations. Herein, the working mechanisms of MEENGs reported so far are comprehensively compared. Subsequently, a systematic summary of the materials selection and fabrication methods for currently reported MEENG construction is presented. Then, the improvement strategies and development directions of MEENG are provided. At last, the demonstrations of the applications assembled with MEENGs are extracted. This work aims to pave the way for the further MEENGs to break through the performance limitations and promote the popularization of future micron electronic self‐powered equipment. Abstract : This review focuses on the recent development of moisture‐enabled‐electric nanogenerators (MEENGs), which are distinguished from traditional hydropower production by directly generating electricity from ubiquitous moisture in the natural environment. In addition, MEENGs are also promising for next‐generation portable self‐powered or battery‐free systems, enabling the creation of a new range of intelligent device components to upgrade artificial intelligence and Internet of Things applications.